Mitochondrial damage and IL-1β production in monocytes caused by Neospora caninum infection are mediated by dense granule protein 7 and prohibitins - Chen, Yu; Shimoda, Naomi; Nihei, Coh-ichi; Sawa, Ryuichi; Takahashi, Yuko; Nishigori, Mitsuhiro; Nakamura, Shu; Liu, Jingwei; Koshiba, Takumi; Ushio-Watanabe, Nanako; Nishikawa, Yoshifumi (Frontiers in Immunology, 2025)
IntroductionThe intracellular proliferation of Neospora caninum tachyzoites and the host immune response against infection are key steps in the pathogenesis of neosporosis. However, the molecules responsible for the activation of the inflammasome induced by N. caninum infection have not been identified.MethodsIn the infection of human monocytic cell line THP-1 cells with the N. caninum dense granule protein 7 knock-out (NcGRA7KO) parasite and the parental strain Nc1, production of IL-1β and TNF-α, phosphorylated NF-κB p65 were measured. LC‒MS/MS analysis of NcGRA7 immunoprecipitates, mitochondrial fractionation and proteolysis assays were also performed.ResultsIn the infection of THP-1 cells with the NcGRA7KO parasite, decreased IL-1β release was observed compared with Nc1 infection. Transfection with plasmids for reconstitution of the NLRP3 inflammasome enhanced IL-1b production via additional transfection with NcGRA7 cDNA. NLRP3 inhibitor, CASP1 inhibitor, and NF-κB inhibitor significantly suppressed IL-1β production induced by Nc-1 infection, whereas no inhibitory effect was observed in NcGRA7KO-infected cells. Furthermore, treatment with any of the inhibitors led to a reduction in TNF-α production in both Nc-1- and NcGRA7KO-infected cells. Western blot analysis of phosphorylated NF-κB p65 demonstrated that N. caninum infection induced NF-κB p65 phosphorylation; however, no significant difference was observed between Nc1-infected and NcGRA7KO-infected cells. Infection of the THP-1 cells with NcGRA7KO parasites decreased the host mitochondrial damage and apoptosis in THP-1 cells compared to infection with Nc1, suggesting that NcGRA7 plays a crucial role in the pathogenesis of N. caninum. Furthermore, LC‒MS/MS analysis of NcGRA7 immunoprecipitates identified NcGRA7-binding proteins in host cells that localize to host mitochondria. Additionally, mitochondrial fractionation and proteolysis assays using proteinase K showed the distribution of NcGRA7 from the inner mitochondrial membrane to the matrix of host mitochondria. Interestingly, NcGRA7 formed a complex with the prohibitins PHB1 and PHB2. Using inhibitors of PHB1 or transfecting N. caninum-infected THP-1 cells with PHB1 siRNA significantly decreased IL-1β production, but not TNF-α.DiscussionThese findings indicate that NcGRA7 does not directly modulate NF-κB activation but likely enhances the production of IL-1β and TNF-α through post-transcriptional mechanisms, thereby contributing to the upregulation of NLRP3 expression. Moreover, our results suggest that NcGRA7 influences both the NF-κB and inflammasome pathways through its interaction with host cell prohibitins. Elucidating the roles of PHB1 and NcGRA7 will provide new insights into the host–parasite interactions underlying N. caninum pathogenesis.